Targeted outdoor residual spraying, autodissemination devices and their combination against Aedes mosquitoes: field implementation in a Malaysian urban setting. Issue 6 (15th December 2020) - Hamid, Nurulhusna Ab; Alexander, Neal; Suer, Remco; Ahmed, Nazni Wasi; Mudin, Rose Nani; Omar, Topek; Dapari, Rahmat; Che Mat Din, Shahrom Nor Azian; Rahman, Roslinda Abdul; Jaraee, Ropiah; Baur, Frederic; Schmitt, Frederic; et al.
Abstract: Currently, dengue control relies largely on reactive vector control programmes. Proactive vector-control using a rational, well-balanced integrated vector management approach may prove more successful for dengue control. As part of the development of a cluster randomized controlled epidemiological trial, a study was conducted in Johor Bahru, Malaysia. The study included one control site (three buildings) and three intervention sites which were treated as follows: targeted outdoor residual spraying only (TORS site, two buildings); deployment of autodissemination devices only (ADD site, four buildings); and the previous two treatments combined (TORS + ADD site, three buildings). The primary entomological measurement was per cent of positive ovitraps—ovitrap index (OI). The effect of each intervention on OI was analyzed by a modified ordinary least squares regression model. Relative to the control site, the TORS and ADD sites showed a reduction in the Aedes OI (−6.5%, P = 0.04 and −8.3%, P = 0.10, respectively). Analysis by species showed that, relative to control, the Ae. aegypti OI was lower in ADD (−8.9%, P = 0.03) and in TORS (−10.4%, P = 0.02). No such effect was evident in the TORS + ADD site. The present study provides insights into the methods to be used for the main trial. The combination of multiple insecticides with different modes of action in one package is innovative, although we could not demonstrate the additive effect of TORS + ADD. Further work is required to strengthen our understanding of how these interventions impact dengue vector populations and dengue transmission.